(untitled) (Journal of Health, Population and Nutrition, 2010)
The purpose of this study was to estimate treatment cost for typhoid fever at two hospitals in Kolkata, India. This study was an incidence-based cost-of-illness analysis from the providers’ perspective. Microcosting approach was employed for calculating patient-specific data. Unit costs of medical services used in the calculation were directly measured from the study hospital by standard method. The study hospitals were selected based on accessibility to data and cooperation. Eighty-three Widal-positive and/or cultureconfirmed patients with typhoid fever during November 2003-April 2006 were included in the study. Most (93%) patients were children. Eighty-one percent was treated at the outpatient department. The average duration of hospitalization for child and adult patients was 8.4 and 4.2 days respectively. The average cost of treating children, adults, and all patients was US 16.72, 72.71, and 20.77 respectively (in 2004 prices). Recalculation based on 80% occupancy rate in inpatient wards (following the recommendation of the World Health Organization) found that the cost of treating children, adults, and all patients was US 14.53, 36.44, and 16.11 respectively. Key words: Costs of illness; Healthcare cost; Treatment cost; Typhoid fever; India DOI: 10.3329/jhpn.v27i6.4323 J Health Popul Nutr 2009 Dec; 27(6): 725-732